States versus markets the emergence of a global economy - Schwartz, Herman M. 1958- (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2010)
"States versus Markets shows that globalization is not a novel phenomenon but a recurrent process whereby markets have, since the sixteenth century, periodically redistributed economic activity. This revised and updated new edition takes account of the new rise of Asia and the global financial crisis originating in the US housing finance system"--Provided by publisher.
States, agriculture, and globalization -- The rise of the modern state : from street gangs to mafias -- States, markets, and the origins of international inequality -- Economic and hegemonic cycles -- The Industrial Revolution and late development -- Agricultural exporters and the search for labor -- Agriculture-led growth and crisis in the periphery : Ricardian success, Ricardian failure -- The collapse of the nineteenth-century economy : the erosion of hegemony? -- The fall and rise and fall again of globalization -- The Depression, US domestic politics, and the foundation of the post-World War II system -- International money, capital flows, and domestic politics -- Transnational firms : a war of all against all -- Industrialization in the old agricultural periphery : the rise of the newly industrialized countries -- Trade, protection, and renewed globalization -- US hegemony : declining from below? -- US hegemony and global stability : reviving or declining from the top down?
Includes bibliographical references and indexes.
Keywords: International economic relations; Industrial policy; Commercial policy